Natural Killer Cells in the Orchestration of Chronic Inflammatory Diseases. (27th March 2017) - Parisi, Luca; Bassani, Barbara; Tremolati, Marco; Gini, Elisabetta; Farronato, Giampietro; Bruno, Antonino
Abstract : Inflammation, altered immune cell phenotype, and functions are key features shared by diverse chronic diseases, including cardiovascular, neurodegenerative diseases, diabetes, metabolic syndrome, and cancer. Natural killer cells are innate lymphoid cells primarily involved in the immune system response to non-self -components but their plasticity is largely influenced by the pathological microenvironment. Altered NK phenotype and function have been reported in several pathological conditions, basically related to impaired or enhanced toxicity. Here we reviewed and discussed the role of NKs in selected, different, and "distant" chronic diseases, cancer, diabetes, periodontitis, and atherosclerosis, placing NK cells as crucial orchestrator of these pathologic conditions.